Fantastic Politics : Art in Times of Crisis. - Bie-Larsen, Bard; Denney Ness, Nina; Hogkvist, Stina; Jortveit, Anne Karin; Kroksnes, Andrea; Nordgren, Sune; Ustvedt, Oystein; Verwoert, Jan; Waallann Hansen, Vibeke; Yvenes, Marianne (Oslo : National Museum of Art, Architecture and Design Oslo, 2006)
Colen, Dan ; Eliasson, Olafur ; Export, Valie ; Fahlström, Öyvind ; Golub, Leon ; Matte, Pierre Lionel ; Metzel, Olaf ; Mir, Aleksandra ; Potrc, Marjetica ; Roepstorff, Kristine ; Sachs, Tom ; Schnitger, Lara ; Slettemark, Kjartan ; Wulffen, Amelie von
biog., ind. tent., gr. tent. p. 168-172
Engels
Noors
Exhibition. Fantastic Politics : Art in Times of Crisis. National Museum of Art, Architecture and Design Oslo. 20-10-2006. 25-2-2007
boek